2017
DOI: 10.1021/acs.macromol.6b01140
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Long-Chain Multication Cross-Linked Anion Exchange Membranes

Abstract: Anion exchange membranes (AEMs) are a promising class of materials that enable non-noble metals to be used as catalysts in fuel cells. Compared to their acidic counterparts, typically Nafion and other perfluorosulfonate-based membranes, the low OH– conductivity in AEMs remains a concern as these materials are developed for practical applications. Cross-linked macromolecular structures are a popular way to optimize the trade-off between the ionic conductivity and the water swelling of AEMs with high ion exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(119 citation statements)
references
References 64 publications
8
106
1
Order By: Relevance
“…This seemed reasonable since the membranes were essentially fully hydrophobic. Interestingly, however, once nickel was added, a broad scattering peak appeared for all samples except for HP4‐5Ni , consistent with the formation of ionic clusters within the network, due to the formation of clustered metal cations . The lack of a second‐order peak indicated that the phase separation did not have long range order, and thus likely arose from ionic clusters.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…This seemed reasonable since the membranes were essentially fully hydrophobic. Interestingly, however, once nickel was added, a broad scattering peak appeared for all samples except for HP4‐5Ni , consistent with the formation of ionic clusters within the network, due to the formation of clustered metal cations . The lack of a second‐order peak indicated that the phase separation did not have long range order, and thus likely arose from ionic clusters.…”
Section: Resultsmentioning
confidence: 62%
“…Six different AEMs were fabricated, three with CP4 and three with HP4 as the crosslinker, where the amount of 3 added was modified so each membrane contained on average either 5, 10, or 20 repeat units of 3 , correlating to 5, 10, or 20 repeat units of nickel cations, between two PS crosslinkers. However, despite increasing the metal content, all three samples had IEC values of around 1 mmol/g, as determined by back titration . Full nomenclature and components of each membrane are shown in Scheme , where the first part of the name indicates which PS crosslinker was used and the number indicates the average repeat units of 3 .…”
Section: Resultsmentioning
confidence: 99%
“…E a values of the 4C‐ y ‐Q membranes are approximately half those of the 8C‐ y ‐Q series, indicating better ion transport channel was established in the 4C‐ y ‐Q type membranes. Moreover, the activation energy barrier of 4C‐60‐Q is 6.61 kJ mol −1 , which is lower than that of Nafion 112 (7.02 kJ mol −1 ) and numerous reported AEMs, implying an obvious enhancement of ion transport in this novel symmetric side‐chain‐type ionomer.…”
Section: Resultsmentioning
confidence: 99%
“…σ/IEC values of 4C‐60‐Q and some reported membranes are shown in Figure . ANM‐22‐100 (IEC = 1.67 mmol g −1 ) and x (QH) 3 QPPO‐40 (IEC = 3.59 mmol g −1 ) membranes showed OH − conductivities comparable to those of Nafion 112 (IEC = 0.91 mmol g −1 ). However, their ionic conduction efficiency remained unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…At high temperatures, strongly electrophilic functional groups are more likely to be attacked by OH À . 2,46 Thus, the IEC retention ratios and conductivity retention ratios of the cross-linked AEMs (CAPSF-N) and APSF membrane sample were tested to evaluate their alkaline stability by calculating the ratio of IEC and the conductivity of the tested AEMs before and aer being soaked in 1 M KOH at 60 C for 15 days. As illustrated in Fig.…”
Section: Alkaline Stabilitymentioning
confidence: 99%